Descrizione e spiegazione nella linguistica storica (Atti del Sodalizio Glottologico Milanese, 2019)
Descriptions and explanations in historical linguistics. The principles underlying language change involve structural, sociocultural and neurocognitive factors, as languages are complex and coherent systems governed by algorithms, at the intersection of nature and nurture. Therefore, in order to understand these principles it is necessary to adopt an interdisciplinary approach in which linguistics could benefit from philology, sociohistorical sciences, physiology and neurosciences. Moreover, there is a need for disentangling the actuation problem from the transition problem, to explain the patterns of language change and its effect on the systems involved. KEYWORDS: Actuation and transition of language change, markedness, frequency, memory system